A 3D finite element model of prophylactic vertebroplasty in the metastatic spine: Vertebral stability and stress distribution on adjacent vertebrae. (2nd January 2020) - Berton, Alessandra; Salvatore, Giuseppe; Giambini, Hugo; Ciuffreda, Mauro; Longo, Umile Giuseppe; Denaro, Vincenzo; Thoreson, Andrew; An, Kai-Nan
Abstract : Background and Objective: Patients with metastatically compromised vertebra can experience pathologic fracture with relevant neurological complications. Vertebroplasty is a low cost procedure and it can potentially prevent neurologic impairment if performed at an early stage. The aim of this study is to evaluate the effects of prophylactic vertebroplasty on stability of the metastatic spine and analyze load distribution at adjacent vertebrae. Setting: A 3D finite element model of two spinal motion segments (L3-L5) was developed. A central core of elements was selected in L4 vertebral body and material properties of a lytic metastasis and successively PMMA were assigned. The model was settled in order to simulate a non-osteoporotic spine and an osteoporotic spine. Outcome Measures: Vertebral stability was assessed by the measurement of vertebral bulge (VB) and vertebral height (VH) on L4. Load transfer on adjacent vertebrae was evaluated by observing the distribution of the von Mises stress on L3 and L5 endplates. Results: The metastasis increased VB by 424% and VH by 626%, while prophylactic vertebroplasty decreased VB and VH by 99% and 95%, respectively, when compared to the normal/non-metastatic model. Prophylactic vertebroplasty increased the average von Mises stress of L3 lower endplate by 1.33% in the non-osteoporotic spine, while it increased to 16% in the osteoporotic model. Conclusions: Prophylactic vertebroplasty could represent an interesting option to improve vertebral strength of metastatically compromised spine without excessively increasing the stresses on adjacent vertebrae in non-osteoporotic spine.